Stories of the Past: Immersive History Museums as Historical Fiction. - Shafer, Emily. (2017)
Abstract: Living history museums, re-enactments of historic events, and historic house museums all offer unique encounters with the past. As “immersive history museums,” these types of institutions can be regarded as the “historical fiction” of the museum field. As such, these museums can and should take some measure of creative license in their interpretations of history. Rather than focusing on minute historical authenticity and factual material, these institutions should strive to create generally historic atmospheres in order to make their content comprehensible and relevant to visitors, simultaneously offering environments in which visitors can fulfill their own objectives unrelated to specific content. Greenfield Village in Dearborn, Michigan, and Museums of Old York in York, Maine, serve as case studies to illustrate instances of appropriate and inappropriate use of creative license in immersive museum settings.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of History.; Advisor: Reed Ueda.; Committee: Andrew McClellan, and Ina Baghdiantz-McCabe.; Keywords: Museum studies, and American history.